Plant derived bioactive compounds and their potential to enhance adult neurogenesis - Krishnapriya; Parameswaran Sasikumar; Maniyamma Aswathy; Prakash Tripathi Prem; Kokkuvayil Vasu Radhakrishnan; Pulikkaparambil Sasidharan Baby Chakrapani (Elsevier, 2022)
Background: Self-renewal and proliferation of neural progenitor cells occur throughout humans' lives. However, aging, stress, and degenerative diseases can hinder or stop the process. If you can accelerate neurogenesis in adults, this is a promising way to recover from neurodegeneration and cognitive impairments. As the demand for a safer and natural therapeutic product has increased over the past decade, medicinal plants seem to be a viable alternative to synthetic medicines. Since early human civilization, various herbs have been used as medicines and are still a basis for different modern medications. With the advancements in science, researchers can isolate the active compounds in an herb and predict these herbs' line of action when used as a drug. Our current knowledge of medicinal plants with neurological functions is many, but only a few are scientifically validated. Method: A review of the scientific literature explaining plants' bioactive compounds that show neurogenesis was executed. All published data till the year 2021 have been taken to consideration. PubMed, Scopus, ScienceDirect, and Google Scholar directories were used to explore literature published using relevant keywords. Results: Plants like Panax ginseng, Lycium barbarum, Acorus tatarinowii, Curcuma longa, Salvia miltiorrhiza, Centella asiatica, Bacopa monnieri, Ginkgo biloba, Cuscuta japonica, Radix Astragali, Hericium erinaceus and Banisteriopsis caapi have shown to induce neurogenesis. Conclusions: The information on plants compiled in this review pertains to those with a therapeutic value that can be used for drug development to cope with neurodegenerative diseases and memory impairment.